Comparing in-patient extracorporeal cardiopulmonary resuscitation to standard cardiac treatment group of extracorporeal membrane oxygenation patients: 8 years of experience at a single institution. (January 2020) - Liem, Spencer; Cavarocchi, Nicholas C; Hirose, Hitoshi
Introduction: Post-cardiac arrest survivals remain low despite the effort of cardiopulmonary resuscitation. Utilization of extracorporeal membrane oxygenation during cardiopulmonary resuscitation (extracorporeal cardiopulmonary resuscitation) can provide immediate cardiovascular support and potentially improve outcomes of patients with cardiac arrest requiring cardiopulmonary resuscitation. There is renewed interest in the use of extracorporeal cardiopulmonary resuscitation due to improved outcomes over the years. Methods: Extracorporeal membrane oxygenation data between 2010 and 2018 were reviewed. Patients with extracorporeal membrane oxygenation placed under cardiopulmonary resuscitation were identified, and demographics, extracorporeal membrane oxygenation survival, survival to discharge, and neurological recovery were retrospectively analyzed with institutional review board approval. Results: Among 230 cases of extracorporeal membrane oxygenation, 34 (21 males and 13 females, age of 49 ± 13 years) underwent extracorporeal cardiopulmonary resuscitation. The mean duration of extracorporeal membrane oxygenation support after extracorporeal cardiopulmonary resuscitation was 8.3 ± 7.9 days. Extracorporeal membrane oxygenation mortality among extracorporeal cardiopulmonary resuscitation patients was 32% (11/34) and hospital survival was 38% (13/34), which are similar to standard cardiac extracorporeal membrane oxygenation (extracorporeal membrane oxygenation survival 62% and hospital survival 39% in cardiac extracorporeal membrane oxygenation). Among the extracorporeal membrane oxygenation death after extracorporeal cardiopulmonary resuscitation, the majority was due to neurological injury (73%, 8/11); 8/34 extracorporeal membrane oxygenation survival rate and 30-day survival rate were 63% and 25% in early half of study (2010-2014) and have improved to 70% and 60% in late half of study (2014-2018). Conclusion: Over years of experience with extracorporeal membrane oxygenation, the outcome of the extracorporeal cardiopulmonary resuscitation has been improving and appears to exceed those of traditional methods, despite limited sample size. Neurological complications still need to be addressed in order for survival and outcomes to improve.